Tumor Microenvironment–Responsive Peptide-Based Supramolecular Drug Delivery System - Zhang, Wenbo; Yu, Lanlan; Ji, Tianjiao; Wang, Chenxuan (Frontiers in Chemistry, 2020)
Physical and biochemical differences between tumor tissues and normal tissues provide promising triggering factors that can be utilized to engineer stimuli-responsive drug delivery platforms for cancer treatment. Rationally designed peptide-based supramolecular architectures can perform structural conversion by responding to the tumor microenvironment and achieve the controlled release of antitumor drugs. This mini review summarizes recent approaches for designing internal trigger-responsive drug delivery platforms using peptide-based materials. Peptide assemblies that exhibit a stimuli-responsive structural conversion upon acidic pH, high temperature, high oxidative potential, and the overexpressed proteins in tumor tissues are emphatically introduced. We also discuss the challenges of current peptide-based supramolecular delivery platforms against cancer.